BREAST SELF-EXAMINATION AWARENESS AND PRACTICES AMONG FEMALE UNIVERSITY STUDENTS IN RIVERS STATE, NIGERIA - Amadi, Gabriel Uchechi (International Journal of Contemporary Health Sciences and Technology, 2024)
This study investigated the correlates of breast selfexamination among female students in public universities, Rivers State. A descriptive correlational research design was adopted for this study with a population consisting of forty-four thousand, eight hundred and sixty-four (44,864) female university undergraduates in Rivers State. A sample size of 1,200 was selected using a multi-stage sampling procedure. The instrument for data collection was a structured questionnaire with a reliability coefficient of 0.74. Data collected were analyzed using point biserial correlation and regression analysis at 0.05 level of significance. The finding of the study showed that the level of practice of breast self-examination among female undergraduates in higher institutions in Rivers State was low (38.2%). Statistically significant relationship was found between practice of breast self-examination and variables such as family history of breast cancer [f(1,1172) = 9051.85, p<0.05], selfefficacy [f(1,1172) = 4187.78, p<0.05], perceived susceptibility [f(1,1172) = 4820.23, p<0.05], and attitude [f(1,1172) = 4925, p<0.05]. It was concluded that the practice of breast self-examination among female students in public universities, Rivers State was low and factors correlated with their practice were: family history of breast cancer, self-efficacy, perceived susceptibility, and attitude. It was recommended among others that, healthcare institutions should help the family members of their patients with breast cancer by assigning health officers to their families to counsel, teach and monitor them practice BSE, and undergraduate students should enhance their self-efficacy by taking out time to learn it constantly until they are able to do it appropriately